Analisis Pelaksanaan Urbun dalam Sewa-Menyewa Kontrakan Berdasarkan Teori Maslahah - Desy Deria; Irwan Setiawan (Jurnal Al-fatih Global Mulia, 2022)
Humans are social creatures who need one individual to another. Therefore, humans cannot live alone without others' services or assistance. They meet each other in order to meet their daily needs, one of which is by renting. The problem of rented rent that occurs in Cikarang Pusat, Bekasi is the practice of applying down payments according to Maslahah theory. Renting is a form of muamalah activity that humans often do to make ends meet. This need can be in the form of benefits of goods or services that they do not have, such as renting a temporary residence. Some people in Cikarang Pusat, Bekasi rented houses for temporary living by applying down payment. Meanwhile, the majority of Ulama argued that the application of down payment is prohibited and the law is invalid for it contains gharar (vagueness) elements. This study aims to investigate the application of down payment in rent in Cikarang Pusat, Bekasi according to maslahah theory. This research is a qualitative descriptive research with interview and documentation data collection methods. The research documentation used references relating to rent, down payments and others related to this research. The results of this study indicated that the application of down payment in rented rent in Cikarang Pusat Bekasi was done through paying a portion of the money at the beginning of the rent as a sign of it. The remaining payment then was paid at a later date according to the agreement. If the tenant continued the rent, the down payment would be counted as rent payment. However, if the tenant canceled the transaction, the down payment became the property of the landlord. In applying this down payment, there were parties who felt aggrieved by both the landlord and the tenant. It was allowed, because there were provisions related to down payment stated in the Compilation of Sharia Economic Laws; if the transaction cancellation was carried out by the tenant, the down payment was no needed to be returned by the landlord. However, if the cancellation was made by the landlord, the down payment had to be returned to the tenant. In addition, it was carried out with the aim of avoiding any broken promises between the landlord and the tenant.